Global Trends and Research Collaborations on Food and Beverages Warning Labels: A Bibliometric Analysis - Hernández-Vásquez, Akram (2024)
Background: Non-communicable diseases (NCDs) represent a global health challenge, accounting for 74% of deaths worldwide. One of the recommended interventions to reduce the risk of NCDs is the implementation of warning labels (WLs) on food products to alert consumers about high levels of undesirable nutrients, such as sugar or saturated fats. We aimed to conduct a bibliometric analysis of scientific literature related to WL policies in food and beverages to evaluate global trends and collaborations. Methods: A bibliometric analysis was performed using the Web of Science Core Collection (WoSCC). Articles published between 1998 and 2023 were retrieved using the search terms “warning labels” AND “food” OR “beverage”. Bibliometric indicators, including publication counts, citations, collaborations, and thematic trends, were analyzed using the Bibliometrix package in R and VOSviewer. Results: We included 255 articles on WLs. Scientific production increased markedly from 2018 onwards, with over 30 articles published annually from 2018 to 2023. The most cited article, by Taillie et al., focused on the impact of Chile’s WL policies. The United States had the largest scientific production, followed by Brazil and Chile. Nutrients was the journal with the most publications on this topic. Conclusions: The growth in WL-related research, particularly in Latin America, reflects the increasing implementation of these policies. These results underscore key collaborations and evolving research themes, from food labeling to broader public health impacts, emphasizing the need for continued evaluation of WL effectiveness.